Ordem dos Advogados do Brasil: diagnósticos dos desafios e perspectivas para a efetivação de uma agenda ambiental no estado do Tocantins - Lustosa, Kárita Barros (Universidade Federal do Tocantins, 2018)
The present dissertation and respect to one of the central themes central themes to the realization of human rights: the right to a healthy and balanced environment. This is broad subject, with multiplicity of subdivisions due to the complexity of the subject, having been delimited the object of study in the investigation of the role and performance of the Order of Lawyers of Brazil – OAB, for the development and strengthening of actions directed to the institutionalization of the environmental theme in the organ, with a delimited analysis, due to the comprehensiveness of the subject and the territorial commercial dimension of Brazil, in relation to the Tocantins Section. The research approach was based on the need to develop sustainable actions in the use of natural resources by the public or private segments, in what is included in the OAB, before the recognized function of providing public service directed to the collective well-being. In the methodological strategy, with the use of a case study, a deductive and qualitative approach was used, analyzing the OAB-TO, notably, in the institutional, in the institutional scope, to act by encouraging actions aimed at building an environmentally balanced society. The technical procedures were documentary research, which included legislation of the analyzed institution and research of works related to the environmental problem. The core of the study was the performance of OAB-TO, through the Environmental Law Commission, and the institutionalization of sustainable postures, sedimentando their contribution in favor of the environment.